1993
DOI: 10.1159/000218303
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone, Etoposide and Prednisolone (NOVEP) in Previously Untreated Elderly Patients with Non-Hodgkin’s Lymphoma (NHL) and as Salvage Therapy for Refractory NHL

Abstract: Background: Elderly patients with non-Hodgkin’s lymphoma (NHL) are often excluded from or underrepresented in clinical trials of combination chemotherapy regimens because of toxicity of the treatment. Materials and Methods: We report our results in a cohort of 32 patients aged over 60 years who received mitoxantrone, etoposide and prednisolone as first-line therapy and of another 14 patients with relapsed NHL as salvage therapy. 26 patients had high-grade NHL and 20 had low-grade NHL. Advanced stage was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A similar result was observed by the Italian Multiregional Non-Hodgkin's Lymphoma Study Group.l85) Recently, a German group recommended 8 cycles of the NOVEP regimen every 3 weeks (mitoxantrone 12 mg/m 2 intravenously day 1, etoposide 120 mg/m 2 intravenously days I to 3 and prednisone 50 mg/m 2 orally days 1 to 5) in previously untreated patients. [86) A retrospective analysis of patients older than 80 years of age, corresponding to 5.4% of alllymphoma patients, demonstrated that the tolerance of standard treatments is a major problem in this population of patients with different types and stages ofNHL. [87) For treatment of multiple myeloma, 4 generations of regimens are available, namely: • The first generation melphalan/prednisone regimen; • The second generation combination chemotherapies [vincristine, melphalan, cyclophosphamide, prednisone (VMCP); vincristine, carmustine, doxorubicin, prednisone (VBAP); doxorubicin, carmustine, cyclophosphamide, melphalan (ABCM)]; • The third generation intensified chemotherapy [vincristine, doxorubicin, dexamethasone (VAD)], or high dose glucocorticoids or intermediate dose cyclophosphamide; • The fourth generation autologous or allogenic bone marrow transplantation.…”
Section: Non-hodgkin's Lymphoma Multiple Myeloma and Hairy Cell Leukmentioning
confidence: 99%
“…A similar result was observed by the Italian Multiregional Non-Hodgkin's Lymphoma Study Group.l85) Recently, a German group recommended 8 cycles of the NOVEP regimen every 3 weeks (mitoxantrone 12 mg/m 2 intravenously day 1, etoposide 120 mg/m 2 intravenously days I to 3 and prednisone 50 mg/m 2 orally days 1 to 5) in previously untreated patients. [86) A retrospective analysis of patients older than 80 years of age, corresponding to 5.4% of alllymphoma patients, demonstrated that the tolerance of standard treatments is a major problem in this population of patients with different types and stages ofNHL. [87) For treatment of multiple myeloma, 4 generations of regimens are available, namely: • The first generation melphalan/prednisone regimen; • The second generation combination chemotherapies [vincristine, melphalan, cyclophosphamide, prednisone (VMCP); vincristine, carmustine, doxorubicin, prednisone (VBAP); doxorubicin, carmustine, cyclophosphamide, melphalan (ABCM)]; • The third generation intensified chemotherapy [vincristine, doxorubicin, dexamethasone (VAD)], or high dose glucocorticoids or intermediate dose cyclophosphamide; • The fourth generation autologous or allogenic bone marrow transplantation.…”
Section: Non-hodgkin's Lymphoma Multiple Myeloma and Hairy Cell Leukmentioning
confidence: 99%